Stress and Coping Strategies Among Parents of Neonates Admitted in Neonatal Intensive Care Unit – a Hospital-Based Study - Maharjan, Ramu; Shrestha, Mangala; Pokharel, Nirmala; Rai, Gayatri; Karn, Basant; Chaudhary, Kriti; Adhikari, Bikram (Journal of Karnali Academy of Health Sciences, 2022)
Background: Parents can experience feelings of guiltiness, helplessness, distress, fear, and anxiety whose neonates are admitted in Neonatal Intensive Care Unit (NICU) creating stressful family patterns and demanding coping mechanisms. This study aimed to assess stress and coping strategies among the parents of neonates admitted to NICU. Methods: A cross-sectional study was conducted among 60 parents of neonates admitted to NICU of BPKIHS, Dharan. Data was collected using Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU) for stress score, and Brief Coping Orientation to Problems Experienced (COPE) Inventory for coping score through face-to-face interviews and entered and analyzed data in Statistical Packages for Social Sciences (version 16). Categorical variables were presented as frequency and percentage whereas numeric variables as mean and standard deviation, paired t-test was used to compare mean stress and coping scores of parents. An independent sample t-test was used to compare mean stress score and coping strategies with selected demographic variables. Results: Overall parental mean stress score was 3.14±0.48, higher among mothers compared to fathers (3.39±0.43; 2.89±0.37; p-value <0.001). The overall parental mean coping score was 2.79±0.20 (father: 2.79±0.21; mother: 2.79±0.18; p-value=0.922). The mother’s stress score was higher in planned pregnancy (3.47±0.38, p-value=0.04) compared to unplanned (3.11±0.50) and higher in caesarean section (3.55±0.38, p-value=0.04) compared to vaginal delivery (3.23±0.43). The coping score was higher among newborn’s parent with birth-weight ≥ 2.5 kg compared to newborn’s parent with birth-weight < 2.5 kg (father: 2.67±0.23 versus: 2.85±0.19, p-value=0.03; mother: 2.69±0.18 versus 2.83±0.17, p-value=0.04). Conclusion: Neonatal admission to NICU produces a varying degree of stress to the parents primarily due to alteration in a parental role leading to the adoption of various coping strategies.